Mature primary human osteocytes in mini organotypic cultures secrete FGF23 and PTH1-34-regulated sclerostin - Knowles, Helen J.; Chanalaris, Anastasios; Koutsikouni, Argyro; Cribbs, Adam P.; Grover, Liam M.; Hulley, Philippa A. (Frontiers in Endocrinology, 2023)
For decades, functional primary human osteocyte cultures have been crucially needed for understanding their role in bone anabolic processes and in endocrine phosphate regulation via the bone-kidney axis. Mature osteocyte proteins (sclerostin, DMP1, Phex and FGF23) play a key role in various systemic diseases and are targeted by successful bone anabolic drugs (anti-sclerostin antibody and teriparatide (PTH1-34)). However, cell lines available to study osteocytes produce very little sclerostin and low levels of mature osteocyte markers. We have developed a primary human 3D organotypic culture system that replicates the formation of mature osteocytes in bone. The organoids are viable for at least 6 months, allowing co-culture with different cell types and testing of bone anabolic drugs. Bulk RNAseq data displayed the developing marker trajectory of ossification and human primary osteocyte formation in vitro over an initial 8-week period. Vitamin D3 supplementation increased mineralisation and sclerostin secretion, while hypoxia and PTH1-34 modulated sclerostin. Our culture system also secretes FGF23, enabling the future development of a bone-kidney-parathyroid-vascular multi-organoid or organ-on-a-chip system to study disease processes and drug effects using purely human cells. This provides a stable, long-lived, and regulated population of mature human primary osteocytes for a variety of research applications.